Carboplatin, paclitaxel, and pembrolizumab followed by pembrolizumab maintenance for primary treatment of incompletely resected epithelial ovarian cancer - Uyar, Denise; Michener, Chad M.; Bishop, Erin; Hopp, Elizabeth; Simpson, Pippa; Zhang, Liyun; Rader, Janet S.; Rose, Peter G.; Mahdi, Haider S.; Debernardo, Robert; Christian, Qiana; Bradley, William (Frontiers in Oncology, 2024)
Objective Incompletely resected epithelial ovarian cancer represents a poor prognostic subset of patients. Novel treatment strategies are needed to improve outcomes for this population. We evaluated a treatment strategy combining platinum-based chemotherapy with pembrolizumab followed by pembrolizumab maintenance therapy in the first-line treatment after incomplete resection of epithelial ovarian cancer patients. Methods This was a single-arm, non-randomized pilot study of carboplatin, taxane, and immune checkpoint inhibitor, pembrolizumab, followed by 12 months of maintenance pembrolizumab in patients with incompletely resected epithelial ovarian cancer (EOC). Results A total of 29 patients were enrolled and evaluated for efficacy and safety. The best response to therapy was complete response in 16 (55%) patients, partial response in 9 (31%) patients, and 3 (10%) patients with progression of disease. The median progression-free survival (PFS) was 13.2 months. Grade 3 and 4 toxicities occurred in 20% of patients. In all, 7 patients discontinued therapy due to adverse events. Quality-of-life scores remained high during therapy. Response to therapy did not correlate with PD-L1 tumor expression. Conclusions Combination platinum–taxane therapy with pembrolizumab did not increase median progression-free survival in this cohort of patients. Key message EOC is an immunogenic disease, but immune checkpoint inhibitor therapy has yet to impact outcomes. The current study utilized pembrolizumab in combination with standard chemotherapy followed by a maintenance treatment strategy in incompletely resected EOC. Progression-free survival was not extended in this poor prognostic group with combined chemotherapy and immunotherapy. Clinical trial registration https://clinicaltrials.gov/, identifier NCT 027766582.